LABOR INDOOR AIR QUALITY PRESENTATIONS AND EVENTS (Tufts Archival Research Center, 2007)
Confidential; Calendar of Indoor Air Quality Presentations and Events listing scheduled presenters to various local labor unions across the U.S. in 1988.